Capacitive Interferences Modeling and Optimization between HV Power Lines and Aerial Pipelines - Rabah Djekidel; Djillali Mahi (Institute of Advanced Engineering and Science, 2014)
Metal pipelines are widely used for the transport of fluids and liquid and gaseous hydrocarbons. When these pipelines are installed near overhead power transmission lines, AC interference can occur between the high voltage power lines and pipelines. This interference can cause the appearance of induced voltages that present a risk of electric shock to the operator safety, direct effects on the pipeline, such as corrosion of the coating and steel. Evaluation of this coupling is necessary to ensure the safety of personnel and equipment connected to the pipeline. In this paper, an optimization method combining PSO with CSM is proposed to simulate the capacitive coupling between the HV power lines and aerial pipelines and analyze the different factors that affect the level of this coupling, the simulation results were compared with a previous study of specialty, the results are found in good agreement.DOI:http://dx.doi.org/10.11591/ijece.v4i4.6289